ASTUDYONROUTE PLANNING IN LOGISTICS, USING LOAD DISTANCE MODEL (International Journal of Food and Nutritional Sciences, 2022)
The study aimed to identify how route planning for logistic companies can efficiently implemented. Route Planning explains basic transportation strategies and frameworks, as well as crucial functional needs, while considering contemporary changes in distribution planning. Companies may save mileage, fuel use, and carbon emissions by using a route planning system that calculates the most effective routes. Businesses may better recognize unforeseen deviations and communicate proactively to improve service and customer satisfaction since route planning is linked to real vehicle tracking.